La hoja de aire como la búsqueda imposible - Alvarado Vega, Óscar Gerardo (2004)
The text of Joaquín Gutiérrez, La hoja de aire, sets forth from the point of return of a Costa Rican to his country, the search for his true love, and the disaster that is the result of this search. Alfonso is not successful in his search for Teresa, though the insanity that rules him allows him to continue his impossible search. The disregard that is manifested with those who cross his path, is not more than the beginning of what his return to Costa Rica has signified. The author expounds in this short novel what has to be not the renunciation of an impossible dream: the recapturing of his past and the renunciation of a present that is spoiled for him but in which he confronts refuge in hope. The text is at most the development of this hope that Alfonso carries with him.